DAMPAK PERAYAAN EKARISTI TERHADAP PERKEMBANGAN IMAN UMAT DI LINGKUNGAN ST. GREGORIUS - Yan Ajang; Robertus Joko Sulistiyo (Bahasa Indonesia, 2022)
The celebration of the Eucharist is an expression of gratitude for God’s saving work that was accomplished through Jesus Christ. Through the events of the passion, death, and resurrection of Christ became the culmination and goal of from the Eucharist. That is the why Eucharist is the source and pinnacle of the life of the Church. Because in the celebration of the Eucharist there is a mutually reinforcing relationship between the faithfull. In the celebration of the Eucharist people are required to be able to interpret the celebration of the Eucharist as a means to develop their faith towards maturity. However there is a fact that no a few people are less able to interpret the Eucharist as a saving sacrifice of the so that people continue to be passive because of the lack of enthusiansm and encouragement from those closest to them. The aims of the research are (1) to describe the menaing of the Eucharist (2) to describe the development of faith (3) to describe the impact of the celebration of the Eucharist on the development of the faith of the people in the St. Gregory.